Media Design "Detector Marker" based on STEM with Dragon Fruit Peel Extract for Detectionof Formaldehyde Additives at School in Agroecosystem Zone - Slamet Hariyadi; Suratno Suratno; Bevo Wahono; Agung Wijaya Subiantoro; Annisa Dwi Ayu Permatasari (BIOEDUKASI, 2023)
The use of prohibited food additives such as formalin is still often found, especially in the school environment. In fact, based on the 2012 Minister of Health Regulation No. 033, formalin is prohibited as a food additive. This phenomenon requires people to be quite observant in choosing food tools. In addition, many people think that the formalin content test can only be done through the laboratory, the formalin test can also be done by a simple reagent containing anthocyanin on dragon fruit skin. So, the researchers designed a simple STEAM-based media with a natural formaldehyde-detecting ingredient, namely red dragon fruit peel extract. This design is divided into two parts, namely the design of simple steam-based media and the manufacture of natural dragon fruit peel extract to detect the content of formaldehyde additives in food. The design was carried out by Grade VIII students at SMP Negeri 6 Jember. The final tool produced is a detector marker.